Applying an Exposome-Wide (ExWAS) Approach to Cancer Research - Juarez, Paul D.; Matthews-Juarez, Patricia (Frontiers in Oncology, 2018)
Traditional research approaches, including genome-wide association studies (GWAS), epigenome-wide association studies (EWAS) and Gene × Environment (G × E) studies are limited in their ability to handle the multiplicity of chemical and non-chemical toxicants to which people are exposed in the real world, over their life course, their impact on epigenomics and other biological systems, and their relationship to cancer onset, progression, and outcomes. Exposome-wide association study (ExWAS) provides a new approach for conceptualizing the roles and relationships of multiple chemical and non-chemical exposures in the etiology and progression of cancer at key developmental periods, over the life course, and across generations. ExWAS challenges us to consider the influence of both internal and external environment, chemical and non-chemical stressors, risk and protective factors, and spatial and temporal dimensions of exposures in our models of cancer incidence, outcomes, and disparities. Applying an ExWAS approach to cancer and cancer disparities research supports robust computational models and methods that will allow for analysis of the dynamic and complex interactions between genetics, epigenetics, and exposomics factors. In the coming months, we will spatially and temporally align environmental exposures with SCCS participant data from time of enrollment forward to move us closer to identifying complete exposure pathways that lead to cancer. In the future, we hope to link external sources of exposure to biomarkers of exposure, biomarkers of disease, disease phenotypes, and population level disparities.